O campo de pesquisa da economia solidária no Brasil: Abordagens metodológicas e dimens\~oes analíticas - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The paradigm of solidarity economy emerged at the end of the twentieth century as a proposal of self-management organization of work and production that involves a set of collective practices in search of new strategies of social inclusion and territorial development. Since then, it has become consolidated as a new field of research in several areas of scientific knowledge, not restricted to the social sciences. The purpose of this paper is to identify and characterize a scientific publication in indexed journals involving the field of solidarity economy in its various dimensions. It was tried to emphasize the methodological approaches used by the authors, the areas of knowledge and the main objects of analysis. This article aims at helping to understand a general picture about the production profile in the field of research, as well as new questions for new research, given a complexity of problems related academically related to the theme.
Keywords: J23; Z13; 330; solidarity economy; bibliometric research; self-management; social inclusion; social development